Electron-positron pairs and radioactive nuclei production by irradiation of high-Z target with γ-photon flash generated by an ultra-intense laser in the λ^{3} regime - David Kolenatý; Prokopis Hadjisolomou; Roberto Versaci; Tae Moon Jeong; Petr Valenta; Veronika Olšovcová; Sergei Vladimirovich Bulanov (Physical Review Research, 2022)
This paper studies the interaction of laser-driven γ photons and high-energy charged particles with high-Z targets through Monte Carlo simulations. The interacting particles are taken from particle-in-cell simulations of the interaction of a tightly focused ultra-intense laser pulse with a titanium target. Lead is chosen as the secondary high-Z target because of its high cross-section of the giant dipole resonance and electron-positron pair production. The results reveal an ultra-short, ultra-relativistic collimated positron population and their energy spectra, angular distribution, and temporal profile are found. We investigate the target thickness dependence of the resulting total numbers and total kinetic energies of various particle species emitted from the lead target irradiated with laser-generated γ photons and charged particles separately. We plot the charts of residual high-Z nuclides generated by irradiation of the lead target. Because of the short pulse duration, the γ photon, electron-positron, and neutron sources could find applications in material science, nuclear physics, laboratory astrophysics, and as injectors in laser-based accelerators of charged particles.